Peranan Teknologi Informasi Dalam Mengefektifkan Keputusan Pemberian Dana Corporate Social Responsibilty (CSR) - Elvitrianim Purba (STMIK Budi Darma, 2018)
Information technology is growing increasingly provide convenience to the wearer. One of the ease with which it is offered is to provide the best alternative solution to the decision maker, in this case, the leader. So that leaders can with better and maximum in providing a decision. Applying the method in the desired decision processing is sufficiently good, and speeds up decision processing with the help of the information technology. In this study, researchers discuss the effectiveness of decisions generated by the leadership in terms of decisions grantors Corporate Social Responsibility (CRS). The method used to be applied in decision support system is WASPAS. It is expected that the result of this decision will give maximum effect to the leader in deciding the recipient village of CSR fund